Application of Integrated Drug Screening/Kinome Analysis to Identify Inhibitors of Gemcitabine-Resistant Pancreatic Cancer Cell Growth. (September 2018) - Krulikas, Linas J.; McDonald, Ian M.; Lee, Benjamin; Okumu, Denis O.; East, Michael P.; Gilbert, Thomas S. K.; Herring, Laura E.; Golitz, Brian T.; Wells, Carrow I.; Axtman, Allison D.; Zuercher, William J.; Willson, Timothy M.; et al.
Continuous exposure of a pancreatic cancer cell line MIA PaCa-2 (Mia S ) to gemcitabine resulted in the formation of a gemcitabine-resistant subline (Mia R ). In an effort to discover kinase inhibitors that inhibited Mia R growth, Mia R cells were exposed to kinase inhibitors (PKIS-1 library) in a 384-well screening format. Three compounds (UNC10112721A, UNC10112652A, and UNC10112793A) were identified that inhibited the growth of Mia R cells by more than 50% (at 50 nM). Two compounds (UNC10112721A and UNC10112652A) were classified as cyclin-dependent kinase (CDK) inhibitors, whereas UNC10112793A was reported to be a PLK inhibitor. Dose–response experiments supported the efficacy of these compounds to inhibit growth and increase apoptosis in 2D cultures of these cells. However, only UNC10112721A significantly inhibited the growth of 3D spheroids composed of Mia R cells and GFP-tagged cancer-associated fibroblasts. Multiplexed inhibitor bead (MIB)–mass spectrometry (MS) kinome competition experiments identified CDK9, CLK1-4, DYRK1A, and CSNK1 as major kinase targets for UNC10112721A in Mia R cells. Another CDK9 inhibitor (CDK-IN-2) replicated the growth inhibitory effects of UNC10112721A, whereas inhibitors against the CLK, DYRK, or CSNK1 kinases had no effect. In summary, these studies describe a coordinated approach to discover novel kinase inhibitors, evaluate their efficacy in 3D models, and define their specificity against the kinome.